If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3i + 5 = 9i + 2 Reorder the terms: 5 + 3i = 9i + 2 Reorder the terms: 5 + 3i = 2 + 9i Solving 5 + 3i = 2 + 9i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-9i' to each side of the equation. 5 + 3i + -9i = 2 + 9i + -9i Combine like terms: 3i + -9i = -6i 5 + -6i = 2 + 9i + -9i Combine like terms: 9i + -9i = 0 5 + -6i = 2 + 0 5 + -6i = 2 Add '-5' to each side of the equation. 5 + -5 + -6i = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -6i = 2 + -5 -6i = 2 + -5 Combine like terms: 2 + -5 = -3 -6i = -3 Divide each side by '-6'. i = 0.5 Simplifying i = 0.5
| -3+6x+7x=-27 | | 2x+14=80 | | (-3x+4)=-8(x-3) | | (-3x+4)=-8x-3 | | (x+3)(x-3)=(x-5)(x-3) | | 84-3x^2=x^2 | | 4x+155=11x-6 | | 40x+12y=600 | | -6p-4(4-3p)=4(p-4)-10 | | 9r+16=5 | | 4w^2+16w+15= | | 0=ln(cos(2x)) | | 5x+4=2+4x | | 5x-2+3x=8x-2 | | 3x^3+2x^2-27x-18=x | | 50=5n*2 | | 4x^2+441x+729=0 | | 6b-2b-7=13 | | 6x^2-1x=0 | | (c-10)=3 | | 82=10x(x-1)+22+4x+14 | | -8x-4+4x=-2-4x | | 3x+6x-3+7=30 | | 5.7x-1.8=9.6 | | 8x+4Y=252 | | 6y=6y+35 | | 2x-7=x+14 | | (7)(13)(6)(x)=(57)(19) | | -(8y+3)-(-7y-7)=3 | | (2x^2-4x)(x+3)=0 | | 14x+21=23x+11 | | -3+4=-62 |